Pathogenesis of Systemic Sclerosis - Pattanaik, Debendra; Brown, Monica; Postlethwaite, Bradley C.; Postlethwaite, Arnold E. (Frontiers in Immunology, 2015)
SSc is one of the most complex systemic autoimmune diseases. It targets the vasculature, connective tissue producing cells (namely fibroblasts/myofibroblasts), and components of the innate and adaptive immune systems. Clinical and pathologic manifestations of SSc are the result of: (1) innate/adaptive immune system abnormalities leading to production of autoantibodies and cell-mediated autoimmunity, (2) microvascular endothelial cell/small vessel fibroproliferative vasculopathy, and (3) fibroblast dysfunction generating excessive accumulation of collagen and other matrix components in skin and internal organs. All three of these processes interact and affect each other. The disease is heterogeneous in its clinical presentation that likely reflects different genetic or triggering factor (i.e., infection or environmental toxin) influences on the immune system, vasculature, and connective tissue cells. The roles played by other ubiquitous molecular entities (such as lysophospholipids, endocannabinoids, and their diverse receptors and vitamin D) in influencing the immune system, vasculature, and connective tissue cells are just beginning to be realized and studied and may provide insights into new therapeutic approaches to treat SSc.